(untitled) (Eurasian Journal of Philology Science and Education, 2022)
In the question of language, almost all studies of the history of language cannot go beyond the monuments of the Middle Ages. These ancient artifacts allow us to consider our language in historical, cultural and cognitive terms as a whole, to prove the commonality of the Turkic languages. Even many phenomena in the vocabulary and grammatical structure of words can be identified from the language data of written literary monuments. It is noted that the exhibits of the XI-XI centuries reflect the historical events that have left an indelible mark on the spiritual space of the Turkic peoples (Kazakh), the life, culture, worldview of their people, reveal the huge potential of Turkic languages and show the course of historical development of the language. It is proved that the writings of the XI-XII centuries are not only the product of creativity that tells about the inner world of the poet, but also a source of invaluable wealth and information about the culture and existence of the people who lived in that period, who were the mainstays of the ethnic composition of the modern Turkic peoples. The article is devoted to one of the important and relevant directions in modern science – cognitive linguistics. The author reveals the nature and origins of the concepts, based on the monument of writing of the Middle Ages “Respect of truth” Akhmed Iugneki. The article notes that the language of A.Iugneki’s work is distinguished by its artistry, and at the same time it reliably reflects the historical situation of that era, the life of the people, describes the events that influenced the national consciousness, the national essence of the Turkic-speaking peoples. Research and analysis of the conceptual basis and linguistic features of this historical text is necessary in order to understand the social existence of modern Turkic peoples, including the peculiarities of cognition of the Kazakh people.